SOFT SKILLS BERBASIS BUDAYA LOKAL UNTUK PENDIDIKAN CALON GURU SMK DI SUMATERA UTARA - Muhammad Amin (Jurnal Kependidikan, 2016)
AbstractThe study aims to find the softskills attributes based local culture that can be used as a learning activity supleman on vocational teacher candidates in North Sumatera, and to determine the level of relevance of each attribute of soft skills in several locations in North Sumatra. This study uses two stages of implementation, namely the exploration stage and the verification stage attribute of soft skills. Exploration carried out to find the attributes of soft skills in dominant ethnic groups the considered in the region of North Sumatra which include: ethnic Batak, Malay, Javanese and Minang.  The verification activities involved 126 teachers spread in 12 vocational schools in North Sumatra. The results showed that there were 15 attributes of soft skills based local culture relevant in North Sumatra can used as a supplement to learning vocational teacher candidates. The verification results shown that the relevance of softskills attributes are high category. The result of relevance level differences between regions/locations, shows that all the attributes of soft skills have the same  degree of relevance to each region, so that all the attributes of soft skills can be integrated in the learning regardless of the specific location.